Know your full potential: Quantitative Kelvin probe force microscopy on nanoscale electrical devices - Axt, Amelie; Hermes, Ilka M.; Bergmann, Victor W.; Tausendpfund, Niklas; Weber, Stefan A. L. (Beilstein Journal of Nanotechnology, 2018)
In this study we investigate the influence of the operation method in Kelvin probe force microscopy (KPFM) on the measured potential distribution. KPFM is widely used to map the nanoscale potential distribution in operating devices, e.g., in thin film transistors or on cross sections of functional solar cells. Quantitative surface potential measurements are crucial for understanding the operation principles of functional nanostructures in these electronic devices. Nevertheless, KPFM is prone to certain imaging artifacts, such as crosstalk from topography or stray electric fields. Here, we compare different amplitude modulation (AM) and frequency modulation (FM) KPFM methods on a reference structure consisting of an interdigitated electrode array. This structure mimics the sample geometry in device measurements, e.g., on thin film transistors or on solar cell cross sections. In particular, we investigate how quantitative different KPFM methods can measure a predefined externally applied voltage difference between the electrodes. We found that generally, FM-KPFM methods provide more quantitative results that are less affected by the presence of stray electric fields compared to AM-KPFM methods.
Keywords: AM-KPFM; AM lift mode; AM off resonance; AM second eigenmode; cross section; crosstalk; field effect transistor; FM-KPFM; frequency modulation heterodyne; frequency modulation sideband; quantitative Kelvin probe force microscopy; solar cells